Social psychology: handbook of basic principles - Kruglanski, Arie W.; Higgins, E. Tory (Guilford Press, 2007)
[Pt.] I. BIOLOGICAL SYSTEM -- 1. Evolutionary theory for social and cultural psychology / Linnda R. Caporael -- 2. Visceral and somatic indexes of social psychological constructs : history, principles, propositions, and case studies / Jim Blascovich and Mark D. Seery -- 3. Social cognitive neuroscience : historical development, core principles, and future promise / Kevin N. Ochsner -- [Pt.] II. COGNITIVE SYSTEM -- 4. Prediction : the inside view / David Dunning -- 5. Expectancy / Neal J. Roese and Jeffrey W. Sherman -- 6. The principles of social judgment / Arie W. Kruglanski and David Sleeth-Keppler -- 7. Automatic thought / Susan M. Andersen ... [et al.] -- 8. Information ecology and the explanation of social cognition and behavior / Klaus Fiedler -- 9. Knowledge activation / Jens F(c)œrster and Nira Liberman -- 10. Causal explanation : from social perception to knowledge-based causal attribution / Denis Hilton -- 11. The role of metacognition in social judgment / Richard E. Petty ... [et al.] -- 12. Standards / Monica Biernat and Scott Eidelman -- 14. Decisions constructed locally : some fundamental principles of the psychology of decision making / Eldar Shafir -- 15. Psychological distance / Nira Liberman, Yaacov Trope, and Elena Stephan -- [Pt.] III. PERSONAL MOTIVATIONAL SYSTEM -- 16. Feelings and phenomenal experiences / Norbert Schwarz and Gerald L. Clore -- 17. The role of impulse in social behavior / Fritz Strack and Roland Deutsch -- 18. Social identity and self-regulation / Daphna Oyserman -- 19. Value / E. Tory Higgins -- 20. Basic human needs / Thane S. Pittman and Kate R. Zeigler -- 21. The goal construct in social psychology / Ayelet Fishbach and Melissa J. Ferguson -- 22. Self-regulation and the executive function : the self as controlling agent / Roy F. Baumeister, Brandon J. Schmeichel, and Kathleen D. Vohs -- 23. Self-interest and beyond : basic principles of social interaction / Paul A.M. Van Lange ... [et al.] -- [Pt.] IV. INTERPERSONAL SYSTEM -- 24. Attitude change / Gregory R. Maio and Geoffrey Haddock -- 25. Foundations of interpersonal trust / Jeffry A. Simpson -- 26. The psychology of negotiation : principles and basic processes / Carsten K.W. De Dreu ... [et al.] -- 27. Grounding communication : synchrony / G(c)ơn R. Semin -- 28. Attachment theory and research : core concepts, basic principles, conceptual bridges / Phillip R. Shaver and Mario Mikulincer -- 29. Social power / Susan T. Fiske and Jennifer Berdahl -- [Pt.] V. GROUP AND CULTURAL SYSTEM -- 30. The social psychology of intergroup relations : social categorization, ingroup bias, and outgroup prejudice / Marilynn B. Brewer -- 31. Social psychology of leadership / Michael A. Hogg -- 32. Dynamical social psychology : finding order in the flow of human experience / Robin R. Vallacher and Andrzej Nowak -- 33. Inclusion and exclusion : implications for group processes / John M. Levine and Norbert L. Kerr -- 34. Cultural processes : basic principles / Chi-yue Chiu and Ying-yi Hong -- [Pt.] VI. APPLICATIONS OF SOCIAL PSYCHOLOGY -- 35. Psychology and the law : reconciling normative and descriptive accounts of social justice and system legitimacy / Tom R. Tyler and John T. Jost -- 36. The reciprocal relation between principles and practice : social psychology and health behavior / Alexander J. Rothman and Peter Salovey -- 37. Contributions of social psychology to clinical psychology : three views of a research frontier / Timothy J. Strauman ... [et al.] -- 38. Consumer behavior and marketing / Eric J. Johnson, Michel Tuan Pham, and Gita Venkataramani Johar -- 39. Psychology and politics : the challenges of integrative levels of analysis in social science / Philip E. Tetlock -- 40. Organizational behavior / Leigh Thompson and Jo-Ellen Pozner -- 41. Social action / Mark Snyder and Allen M. Omoto